Accuracy of auction sale valuations in distressed bank lending decisions in Nigeria - Aluko, Bioye Tajudeen (Journal of Business Economics and Management, 2007)
Of all the sub‐sectors of the national economy, the banking industry and the property market have arguably been most severely affected by the current recession. Thus, the prevailing credit crunch in real estate finance and market conditions have implication for disposal and valuations of real estate for mortgage purposes. The study examined whether forced sale valuations of mortgage properties were a good proxy for their auction sale prices. Relevant data involving 67 auction sales of foreclosed residential property transactions together with their contemporaneous forced sale valuations were pooled together in Lagos Metropolis during the period 1994 to 2003 from sample of estate surveying and valuation/auctioneering firms, the lending institutions and the Nigeria Deport Insurance Corporation. The data obtained were analyzed with the aid of frequency distributions and multiple regression models. The study revealed, amongst others, that forced sale values are not good proxies for auction sale prices as against the conclusions of previous studies on accuracy of open market valuations either in Nigeria or other countries like UK, USA and Australia. The implications of the foregoing conclusions on the lending decisions and valuation profession in the country were further examined in the paper. First Published Online: 14 Oct 2010